HASIL BELAJAR DAN EFIKASI DIRI SISWA SEKOLAH MENENGAH PERTAMA PADA MATA PELAJARAN MATEMATIKA - Fanisa Dina Amalia; Eyus Sudihartinih (Prodi Pendidikan Matematika FKIP Universitas Madura, 2020)
This research is a quantitative descriptive study that aims to determine the level of student self-efficacy in mathematics and the relationship of self-efficacy with student mathematics learning outcomes. The population of this research was 56 junior high school students in Serang, Banten. The sample of this research was 30 students with the sampling technique used was a simple random sampling technique simple. To determine the relationship between student’s self-efficacy and mathematics learning outcomes, a simple linear regression test and Pearson correlation test were performed. The results of this research were the level of student’s self-efficacy is in the medium category and student’s self-efficacy has an influence but not significant on student’s mathematics learning outcomes.